KONSEPSI POKOK TOKOH UTAMA DALAM NOVEL BUNDA KISAH CINTA DUA KODI KARYA ASMA NADIA PENDEKATAN PSIKOLOGI CARL ROGERS - Fatmawati, Fatmawati (Jurnal Sastra Aksara, 2019)
This study aims to describe (1) Organisms, Main Figures in Bunda Kisah Cinta Dua Kodi by Asma Nadia (2) Medan Phenomenal Main Figures in Bunda Kisah Cinta Dua Kodi by Asma Nadia and (3) Self Main Figures in the Novel Bunda Kisah Cinta Dua Kodi. This research is a qualitative-descriptive study. The subject of this research is the novel Bunda Kisah Cinta Dua Kodi by Asma Nadia. This research focuses on issues related to Calr Rogers's psychological approach. Data were analyzed by qualitative description techniques, namely a research procedure with the results of descriptive data presentation in the form of words or sentences in the novel Bunda Cinta Cinta Kodi by Asma Nadia. The method of data collection is done by reading and recording techniques. The results of this study show as the third main form of conception in the novel Bunda Kisah Cinta Dua Kodi by Asma Nadia (1) The main character of a child in a child is characterized by his womb father, the goal of realizing his ideals and upholding science and education and wanting to make his mother happy , the hard work in him proved to his father that he could succeed without his help. (2) The Phenomenal Medan main character faced a problem in his efforts about 2 months more hard work and persevered 'Keke Busana' became a large national Muslim fashion. Currently the Keke Busana product has been distributed as a way of life for more than 500 sales agents. (3) self describes an event and conflict that occurs in the main character, experiencing trial after trial as a form of dominant problems found in the novel Bunda Kisah Cinta Dua Kodi by Asma Nadia. The conclusion of this study is the experience and struggle in the Bunda Kisah Cinta Dua Kodi to be used as learning that experience and suffering are an achievement of a process carried out by someone with hard work and firm stance and not surrender to fate.